Generalization of the Bolus Volume Effect on Piezoelectric Sensor Signals during Pharyngeal Swallowing in Normal Subjects - Miyaoka, Yozo; Ashida, Ichiro; Kawakami, Shin-ya; Tamaki, Yuko; Miyaoka, Satomi (Journal of oral biosciences, 2011)
To generalise the effect of bolus (tea) volume on the piezoelectric sensor (PES) signals during pharyngeal swallowing by general linear models (GLMs), laryngeal movement PES data were recorded from eleven healthy adults while they swallowed one of a wide range of volumes. A PES was attached to the front of the neck to record a laryngeal mechanogram, and then each subject was asked to swallow one of six volumes (10 to 32 mL) of tea after a command. For each swallow, four characteristic points on each PES record were defined and four intervals that spanned these points were measured. GLM-ANOVA analysis revealed statistically significant linear regression coefficients for two ‘volume’ effects and four main ‘subject’ effects. The two linear coefficients of the ‘volume’ effect were 2.5 and 2.7, which suggests that a 10-mL increase in tea volume lengthens these intervals by 25 and 27 ms, respectively.